An integrated analysis of miRNA and mRNA expressions in soybean response to boron stress - Qiang Li; Jiahua Guo; Xuejiao Wang; Xiaoyu Zhao; Kunyu Liu; Xiaohui Feng; Wei Liu; Xuefei Gu; Youwei Che; Guangping Chen; Jianjun Yao; Lijun Li; et al. (PLoS ONE, 2025)
Boron (B) fertilization significantly increased soybean seed yields and is an indispensable micronutrient in soybean growth. However, it is difficult to absorb in soil, which can seriously affect soybean growth. In this study, soybeans were planted under B deficiency and B sufficiency conditions, then physiological and biochemical indicators of soybean seedlings were measured. The results indicated that the antioxidant enzyme activity (SOD, POD, CAT, APX) and malondialdehyde content increased considerably compared with their controls in the leaves and roots, respectively. Among these, the difference in the roots was more significant than in the leaves, suggesting that the root system was more sensitive. Therefore, soybean roots under B stress for 12 hours and 8 days were selected to construct the miRNA library for sequencing. In the three comparison groups, 55 miRNAs were differentially expressed in response to B stress, 22 known miRNAs, and 33 novel miRNAs were identified. Through mRNA-miRNA meta-analysis, miRNA-objective gene pairs consisting of 21 DEGs and 11 miRNAs were identified. The GO functional annotation indicated that stress response genes were mostly concentrated in the items of enzyme activity, ion transport, and metabolic processes, etc. In KEGG of 8d, the objective genes were drastically enriched cyanoamino acid metabolism, glycine, serine and threonine metabolism, phenylalanine metabolism, etc. We further constructed the pathway for cyanide amino acid metabolism under B stress and found that miR408c-5p targeted the gene controlling β -glucosidase 18, and the expression level was notably decreased. It was speculated that B stress hindered soybean growth by inhibiting amino acid metabolism and affecting other metabolic pathways. This study combined miRNAs and mRNAs to identify DEMs and metabolic pathways correlated to B stress. This study provides information that will help elucidate the complex mechanism of the B stress response in soybeans. Moreover, candidate miRNAs and mRNAs could yield new strategies for the development of B-tolerant soybean breeding.